KONSEP IJTIHAD KONTEMPORER DALAM PEMIKIRAN YUSUF AL-QARDAWI DAN RELEVANSINYA BAGI PENGEMBANGAN HUKUM KELUARGA ISLAM - Fahri, Herfin; Rivaldhi, Ahmad Faiq (Al Hakam : The Indonesian Journal of Islamic Family Law and Gender Issues, 2025)
Abstract. This study discusses the concept of contemporary ijtihad in Yusuf al-Qardawi's thought and its relevance to the development of Islamic law in the modern era. The background of this research stems from the reality that the dynamics of human life continue to change in line with advances in science, technology, and globalization. These changes demand renewal in Islamic law so that it remains capable of responding to various new issues that were not found in classical times. In this context, Yusuf al-Qaradawi presents the idea of contemporary ijtihad, which emphasizes a balance between the texts of the Sharia (nash) and the context of social reality (waqi‘), and uses maqāṣid al-syarī‘ah as the basic framework for determining the law. This study uses a qualitative method with a library research approach, through analysis of al-Qaradawi's major works such as Al-Ijtihad fi al-Syari'ah al-Islamiyyah, Fiqh al-Waqi', and Al-Fiqh al-Islami bayna al-Asalah wa al-Tajdid. This approach aims to gain an in-depth understanding of the concept of ijtihad offered by al-Qaradawi and its implications for the renewal of Islamic law. The objective of this study is to outline al-Qaradawi's thinking on contemporary ijtihad, examine its methods and principles, and assess the extent to which these ideas contribute to the development of an adaptive, moderate Islamic law that remains grounded in the fundamental values of the Qur'an and Sunnah. The results of the study show that Al-Qardawi developed a framework of ijtihad based on the principles of balance (tawāzun), ease (taysīr), moderation (wasathiyyah), and collective ijtihad (ijtihād jamā‘ī). His thinking has contributed significantly to the development of Islamic law that is adaptive and responsive to the developments of the era. Keywords: Yusuf al-Qaradawi, contemporary ijtihad, Islamic law.